Real time cerebral perfusion monitoring in acute trauma patients: a preliminary study. Issue 7 (28th February 2016) - Kessel, Boris; Alfici, Ricardo; Korin, Alexander; Olsha, Oded; Dudkiewicz, Mickey; Oren, Meir
Abstract : Background: Management of traumatic brain injury is focused on preventing secondary damage. Early recognition of brain ischaemia may improve the final outcome of the trauma victim. The primary aim of this study was to examine the correlation between peripheral oxygen pulse oximetry and brain oxygen saturation measured by a near infrared oximetry device. A second aim was to evaluate the influence of different factors such as fluid and blood administration on brain tissue oxygenation. Methods: This was a prospective pilot study. Mechanically ventilated trauma patients admitted to the trauma unit had cerebral‐somatic oxygen saturation monitoring. Oximeter readings (rSO2) were prospectively collected and compared with concurrent values for peripheral pulse oximetry (SO2). Data were recorded every 15 min and during interventions such as administration of a fluid bolus and blood administration. All interventions were based on accepted clinical parameters. Results: Thirty‐three patients were enrolled. A total of 210 simultaneous measurements of rSO2 and pulse oximetry values were performed. There was correlation between these two parameters in only one third of patients. Twenty‐seven events of possible brain ischemia, defined as rSO2 values less than 50 or a decrease of more than 20% from the baseline, were observed. In 68 (77.2%) of these measurements there was no decrease of peripheral SO2. Significant increases in rSO2 were observed only during administration of fluid boluses. Conclusions: A cerebral oxygenation monitoring device may recognize the possible events of brain ischaemia which are not reflected by pulse oximetry. Fluid administration was the only factor found to improve brain saturation.